Effect of multi-refresh-rate method on user experience: sustained attention and inattentional blindness - Jieun Cho; Jeunghwan Choi; Cheongil Kim; Jeong Hyeon Park; Sang Chul Chong (Cognitive Research)
Abstract In today's digital world, understanding refresh-rate implications on visual perception and energy consumption is crucial. While high refresh rates enhance motion perception and user experience, they also increase energy usage, prompting the need for adaptive solutions like variable refresh rates. This study examines whether users notice or are affected by reduced refresh rates in task-irrelevant areas and examine whether variable refresh rates compromise a satisfactory display experience. Most participants failed to detect decreases in refresh rate in their peripheral view, and their task performance of the main task, which required sustained attention, remained unaffected. However, when informed of the possible change in the periphery, detection of it improved. In addition, during out-of-the-zone states, people with expectations about the phenomenon may be more likely to falsely report the change in the display. The findings suggest that centrally focused attention limits awareness of peripheral refresh-rate changes, supporting the potential of multi-refresh-rate strategies to optimize energy efficiency without compromising user experience.